Emotion regulation as the mediator of reductions in anxiety and depression in the Unified Protocol (UP) for transdiagnostic treatment of emotional disorders: double-blind randomized clinical trial - Khakpoor,Sahel (2019)
Abstract Objective: An important subject in evaluation of the efficacy of treatments is to examine how the intervention is effective and to identify the consequences of that treatment. In this regard, the current study investigates the role of emotion regulation as the mediator of the treatment outcomes of therapy using the Unified Protocol (UP) for transdiagnostic treatment of emotional disorders. Method: This article describes a double-blind randomized clinical trial. A sample of 26 individuals was selected based on cut-off scores for the Beck Depression Inventory and Beck Anxiety Inventory and their final diagnoses were confirmed with the Anxiety Disorders Interview Schedule for DSM-IV (ADIS-IV). The sample was randomly divided into two groups: control and treatment (13 patients each). The treatment group received 20 one-hour UP sessions. The Beck Depression Inventory, the Beck Anxiety Inventory, and the Difficulties in Emotion Regulation Scale were administered at two stages, pre-treatment and post-treatment. Results: The UP reduced anxiety and depression in patients through improvement in emotion regulation. Furthermore, the results showed that the difficulty engaging in goal-directed behavior and non-acceptance of emotional response subscales were capable of predicting 62% of variance in anxiety scores. In turn, two subscales, difficulty engaging in goal-directed behavior and lack of emotional clarity, predicted 72% of variance in depression scores. Conclusion: Emotion regulation can be considered as a potential mediating factor and as predictive of outcomes of transdiagnostic treatment based on the UP. Clinical trial registration: Iranian Registry of Clinical Trials, IRCT2017072335245N1.